1997
DOI: 10.1111/1467-9566.ep10934417
|View full text |Cite
|
Sign up to set email alerts
|

Control and condoms in commercial sex: client perspectives

Abstract: Indepth interviews were recorded with 24 clients of female sex workers to explore their perspectives on the control of commercial sex encounters. The men saw the encounter as falling into three phases, only the first of which -the decision to have sex -was under their control. Subsequent phases -the negotiation of services and the performance of sex -they argued to be under worker control. The men considered that they acquiesced in worker control because they saw themselves as respectful of a woman's right to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…What can we learn from these analyses for the purpose of policy? The most important conclusion is that a public health policy solely aiming at sex workers as the prime target group negates a major risk factor behind the spread of STDs: the clients' preferences (compare Plumridge et al 1997). The evidence suggests that the persistence of unsafe sexual practices is primarily an effect of the consistent inclination of clients.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…What can we learn from these analyses for the purpose of policy? The most important conclusion is that a public health policy solely aiming at sex workers as the prime target group negates a major risk factor behind the spread of STDs: the clients' preferences (compare Plumridge et al 1997). The evidence suggests that the persistence of unsafe sexual practices is primarily an effect of the consistent inclination of clients.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…At the macro‐level, vulnerability to these health risks is influenced by gender inequality (Bruyn 1992, Heise and Elias 1995), structural barriers resulting from poverty (Campbell 2000) and repressive state policies (Choi and David 2007). At the interpersonal level, they are shaped by interpersonal dynamics including workplace condom‐use norm (Yang et al 2005) and patterns of interaction between sex workers and clients (Plumridge et al 1997). Individual level factors such as AIDS knowledge, perceived risk and perceived fear of HIV infection, and economic pressure resulting from family factors and drug use (Wechsberg et al 2005) have also been found to affect non‐condom use, condom failure and client‐perpetrated violence.…”
Section: Transnational Migrant Sex Workers and Multiple Health Risksmentioning
confidence: 99%
“…Studies have shown that people who might be seen to have done something risky or less than responsible engage in discursive stratagems to resist connotations of moral or social odium. Mothers pre-empt and reformulate advice which might impugn care and treatment of their babies (Heritage and Sefi 1992), people who have unprotected sex resist implications of irresponsibility (Silverman 1997) and men who buy sex exculpate themselves by throwing responsibility for safety on their commercial sex partners (Plumridge et al 1997a(Plumridge et al , 1997b. Sensitivity to the impugnment of self is if anything even greater when it comes to behaviour acknowledged to be risky.…”
Section: Introductionmentioning
confidence: 99%